Response and Remission Rates Following High-Frequency vs. Low-Frequency Repetitive Transcranial Magnetic Stimulation (rTMS) Over Right DLPFC for Treating Major Depressive Disorder (MDD): A Meta-Analysis of Randomized, Double-Blind Trials - Cao, Xu; Deng, Chunshan; Su, Xiaolin; Guo, Yi (Frontiers in Psychiatry, 2018)
Background: High-frequency (HF) repetitive transcranial magnetic stimulation (rTMS) over the left dorsolateral prefrontal cortex (L-DLPFC) is the most widely applied treatment protocol for ma-jor depressive disorder (MDD), while low-frequency (LF) rTMS over the right DLPFC (R-DLPFC) also exhibits similar, if not better, efficacy for MDD. Therefore, a meta-analysis is war-ranted to compare the efficacy of the two protocols for MDD. Method: We searched the literature from 1990 through to August 1, 2017 using MEDLINE, and the literature from 1995 through to August 1, 2017 using EMBASE, PsycINFO, the Cochrane Cen-tral Register of Controlled Trials (CENTRAL), SCOPUS and ProQuest Dissertations & Theses (PQDT). We included randomized controlled trials (RCT) comparing the efficacy of HF rTMS over the L-DLPFC and LF rTMS over the R-DLPFC for MDD, which used response and/or remission rates as the primary endpoints, with and without sham-controlled. Results: (1) The meta-analysis of the response rates was based on 12 studies, including 361 patients with MDD (175 for HF (> 5 Hz) over the L-DLPFC, and 186 for LF (< 5 Hz) over the R-DLPFC; odds ratio = 1.08; 95%, confidence interval = 0.88–1.34). (2) The meta-analysis of the remission rate was based on 5 studies, including 131 MDD patients (64 for HF over the L-DLPFC and 67 for LF over the R-DLPFC; odds ratio = 1.29; 95% confidence interval = 0.54–3.10). Conclusion: Both HF rTMS over the L-DLPFC and LF over the R-DLPFC demonstrated similar therapeutic efficacy for the treatment of patients with MDD. The results suggested that further in-vestigation on treatment efficacy indicators before/during treatment is necessary and helpful for op-timizing a personalized protocol for patients.